Study on the stability of high and steep slopes under deep bench blasting vibration in open-pit mines - Su, Hengyu; Ma, Shu (Frontiers in Earth Science, 2022)
To investigate the stability of high steep slopes under the action of deep bench blasting vibration in an open-pit mine, a mine in Inner Mongolia was used as the engineering background to determine the mechanical parameters of rock specimens using uniaxial and triaxial instruments, and the stability of high steep slopes in this open-pit mine was analyzed by combining field vibration monitoring and numerical simulation. The results show that: according to the field blasting monitoring data, the radial, tangential and vertical directions of the vibration wave are between -1.25~1.25cm/s, and the vibration wave is gradually decaying; combined with the field monitoring data, the Sadovsky regression equation is used for regression analysis and data fitting, and the regression equation corresponding to each direction is obtained, which can provide a basis for the prediction of the vibration intensity of step blasting in the later stage; the static force Under the action of static force, the safety coefficient of this high and steep slope is 1.20, and the displacement of its slip zone through the slope is small, which is about 3.5cm, and the stability of the slope is good; under the action of dynamic blasting load, the overall displacement of the slope is small, and the displacement change decreases with the weakening of vibration wave.